Work values and cultural background: a comparative analysis of work values of Chinese and British engineers in the UK - Shi, Ziteng; Huang, Wei; Liang, Yuhui (Frontiers in Psychology, 2023)
In literature of work-related values and attitudes, it is often argued that different work attitudes could be attributed to different ethnic origins and cultural backgrounds. This perspective article argues that we should avoid a deterministic argument of cultural essentialism and explore how ethnic differences in work values were formed in specifical socioeconomic and cultural contexts. To support this argument, this research conducted in-depth interviews to explore the mechanisms underlying the formation of British and Chinese immigrant engineers’ work values in three dimensions: intrinsic-extrinsic, masculine-feminine, uncertainty avoidance-entrepreneurial risk. The main finding in this paper is that the different social and cultural milieus where both ethnic groups grew up to a large extent contributed to their different work habitus, which further resulted in their different work values. To conclude, this paper contributes to the literature by rejecting the cultural essentialism, which links individual work attitudes with their ethnic/cultural backgrounds in a “deterministic” way.